Integration of Local Wisdom in IPAS Learning for Islamic Awareness, Environment, and Sasak Culture - Mukminah, Mukminah; Hirlan, Hirlan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study examined how Sasak local wisdom was integrated into Natural and Social Sciences (IPAS) learning and how this integration supported students’ awareness of Islamic values, environmental responsibility, and Sasak cultural preservation. A qualitative case study was conducted at a public elementary school implementing the Merdeka Curriculum in Central Lombok, Indonesia. The case involved one principal, two classroom teachers, and 24 fifth-grade students. Data were collected through classroom observations, semi-structured interviews with the principal, teachers, and selected students, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings indicated that Sasak local wisdom had not been integrated systematically into IPAS learning. Teachers experienced difficulties in mapping IPAS learning outcomes onto local cultural practices, relied mainly on textbooks and general examples, and had limited access to relevant learning resources and sustained professional support. Nevertheless, locally grounded practices such as besiru and awig-awig were perceived as making learning more contextual and supporting the internalization of religious, social, cultural, and ecological values. Based on these findings, the study proposes a contextual implementation framework that connects scientific concepts, social phenomena, Islamic values, and Sasak local wisdom through inquiry-based learning, project-based learning, ethnopedagogy, reflection, and holistic assessment. The framework may guide adaptation in elementary schools with similar cultural contexts, although further validation is required before broader implementation.